The effect of different carbon dioxide, temperature and watering regimes on plant growth and seed quality of soybean (Glycine max (L.) Merr.) - Kritzinger, Quenton (University of Pretoria, 2024)
Dissertation (MSc Agric (Agronomy))--University of Pretoria, 2024.